THE INFLUENCE OF ISLAMIC PRIZE BEHAVIOR ON INCOME AND EXPENDITURES AND FAMILY WELFARE (CASE ON THE WIFE WHICH WAS RUNNING IN THE CITY OF MATARAM) - Akhmad Jufri (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
This study aims to determine the effect of Islamic bertijarah behavior on income and expenses as well as family welfare on wives who are bertijarah in the city of Mataram. This research was conducted in the city of Mataram, West Nusa Tenggara. The population of this study was 972 people and the sample taken was 10%, namely 97 people. The data collection method was carried out by structured interviews. Data analysis was carried out using a quantitative approach complemented by intuitive and qualitative analysis. Quantitative data analysis used the Partial Least Square (PLS) analysis method with the SmartPLS version 2.0 M3 program. The results of the study show that Islamic pilgrimage behavior has a positive and significant effect on the wife's income; the wife's income has a positive and significant effect on the wife's expenses; wife's income has a positive but not significant effect on family welfare; and the wife's expenditure has a positive and significant effect on family welfare. The norms in the Qur'an and the Sunnah of the Prophet related to Islamic pilgrimage behavior that are trustworthy, honest, tolerant and do not hoard goods have been well implemented by the wife in making pilgrimages in the Mataram City market. Likewise, the wife's income has been spent in the way of Allah to achieve family welfare in the maqasid sharia perspective.